ANALISIS HUBUNGAN TINGKAT PENERAPAN TEKNOLOGI BUDIDAYA PADA TANAMAN MENGHASILKAN DENGAN PRODUKTIVITAS KEBUN KELAPA SAWIT DI LAHAN PLASMA PIR-TRANS (Studi Kasus di PT. Asian Agri Ukui Kecamatan Ukui Kabupaten Pelalawan) - Ismedi Utomo; Ujang Paman Ismail; Hasan Basri Jumin (DINAMIKA PERTANIAN, 2014)
The main problem faced by the smallholders of oil palm plantations is low productivity and quality of production as a result of low technology application on oil palm cultivation, starting from the use of seeds to harvesting operation. Therefore, the purpose of this study was to analyze the relationship between technology adaption in oil palm cultivation with the productivity of oil palm production in plasma land of PIR-Trans of PT. Asian Agri Ukui in Pelalawan Regency. The method used in this study was survey with purposive sampling, chi-square and Spearman’s rho correlation analysis was used to answer purposes of this study. As a result the chi-square analysis was obtained that chi-square value was greater than chi-square table and Spearman’s rho correlation. The results showed that there was a significant relationship of application technology with productivity of oil palm plantation on Plasma Land of PIR-Trans PT. Asian Agri Ukui in Pelalawan regency.